Duncan Lamont Clinch papers - Clinch, Duncan Lamont, 1787-1849.
Letter copybooks (2 volumes) and order book, relating to Clinch's activities as a commander of American forces at Fort King and other Florida fortifications during the 2nd Seminole War (1834-1836), and reflecting concern over depredations committed by Indians and African Americans, inadequate reinforcements, supplies, arms, and naval support; together with ledger (1859) listing slaves at Clinch's plantation, The Refuge. Includes copies of letters and orders of James Gadsden, Edmund Pendleton Gaines, Robert P. Smith, and Charles M. Thruston.
Soldier, planter, and U.S. congressman, of Georgia.
Collection material in English.
Keywords: Gadsden, James, -- 1788-1858 -- Correspondence; Gaines, Edmund Pendleton, -- 1777-1849 -- Correspondence; Smith, Robert P., -- -1847 -- Correspondence; Thruston, Charles M. -- 1789-1873 -- Correspondence; United States. -- Army -- Officers; United States. -- Army -- Supplies and stores; United States. -- Navy. -- History; African Americans -- Florida; Fortification -- Florida; Indians of North America -- Florida -- Wars; Plantations -- Georgia; Seminole War, 2nd, 1835-1842.; Slavery -- Georgia; Florida -- History, Military; Fort King (Fla.); Plantation owners; Representatives, U.S. Congress -- Georgia; Soldiers